Solid-state fermentation of Apocynum venetum L. by Aspergillus niger: Effect on phenolic compounds, antioxidant activities and metabolic syndrome-associated enzymes - Cao, Cha; Lin, Dengfan; Zhou, Yingjun; Li, Na; Wang, Yiwen; Gong, Wenbeng; Zhu, Zuohua; Liu, Chengwei; Yan, Li; Hu, Zhenxiu; Peng, Yuande; Xie, Chunliang (Frontiers in Nutrition, 2023)
The purpose of the research was to investigated the effect of solid-state fermentation (SSF) with Aspergillus niger on total phenolic content (TPC), total flavonoid content (TFC), antioxidant activities and inhibition activity of metabolic syndrome-associated enzymes in Apocynum venetum L. (AVL) ethanol extract. During the SSF, TPC, TFC, quercetin and kaempferol contents were increased by 1.52, 1.33, 3.64 and 2.22-fold respectively than that of native AVL in ethyl acetate (EA) subfraction of ethanol extract. The highest ABTS·+, DPPH· scavenging activities and inhibitory activity against the α-glucosidase and pancreatic lipase were found in the EA subfractions. Fermentation significantly increased the ABTS·+, DPPH· scavenging and the pancreatic lipase inhibitory activity by 1.33, 1.39 and 1.28 times, respectively. TPC showed a significantly positive correlation with antioxidant activities or inhibition against metabolic syndrome-associated enzymes. This study provides a theoretical basis for producing tea products with enhanced antioxidant property, anti-diabetes and anti-hyperlipidemia.